Prospective evaluation of the performance and interobserver variation in endoscopic ultrasound staging of rectal cancer. Issue 9 (September 2018) - El Hajj, Ihab I.; DeWitt, John; Sherman, Stuart; Imperiale, Thomas F.; LeBlanc, Julia K.; McHenry, Lee; Cote, Gregory A.; Johnson, Cynthia S.; Al-Haddad, Mohammad
Abstract : Background: Treatment and prognosis of patients with rectal adenocarcinoma (RAC) are dependent on accurate locoregional staging. Objectives: The aim of this study was to measure the performance characteristics of rectal endoscopic ultrasound (EUS) compared with surgical pathology, and to assess the interobserver variation of rectal EUS in the staging of RAC. Patients and methods: Patients referred for rectal EUS staging of a recently diagnosed RAC were prospectively enrolled between 2012 and 2016. Tandem EUS exams were performed by two independent endosonographers (ES1 and ES2) blinded to each other's findings. Results: Ninety-five patients were enrolled. Seventy-five (79%) underwent curative intent tumor resection, including 30 without neoadjuvant therapy. In this latter group, the sensitivity, specificity, and accuracy of transrectal ultrasonography staging were 75, 83, and 82% for uT1; 50, 65, and 58% for uT2; 56, 81, and 73% for T3; 72, 44, and 63% for N0, and 38, 75, and 63% for N1, respectively. Experienced operators rendered a more accurate N stage and were less likely to overstage compared with less experienced ones ( P =0.01 and 0.02, respectively). Overall, T staging agreement between endosonographers was substantial ( κ =0.61) and N stage agreement was moderate ( κ =0.45). Conclusion: Rectal EUS is more accurate in staging T1 and T3 tumors compared with T2 tumors. Interobserver agreement of rectal EUS in rectal cancer staging is generally good.